Molecular Typing and Antimicrobial Susceptibility of Methicillin-Resistant Staphylococcus aureus Isolated from Bovine Milk in Tanzania - Jibril Mohammed; Michael Henry Ziwa; Yaovi Mahuton Gildas Hounmanou; Adela Kisanga; Huruma Nelwike Tuntufye (International Journal of Microbiology)
Methicillin-resistant Staphylococcus aureus (MRSA) in raw milk can be transmitted from animals to humans, and in Tanzania raw milk is sold in local markets and consumed as purchased. This study was performed to determine the molecular characteristics and antimicrobial susceptibility pattern of MRSA strains isolated from raw bovine milk sold at local markets in Tanzania. A total of 117 raw milk samples were cultured on Baird-Parker medium to isolate S. aureus and PCR was used for amplification of gltB gene for S. aureus identification and the presence of mecA gene for methicillin-resistant strains. Coagulase-negative (CN) S. aureus were reconfirmed using tube coagulase, DNase, and API Staph tests. MRSA isolates were spa typed whereas antimicrobial susceptibility testing was performed by the disc diffusion method. Forty-six coagulase positives (CP) and two CN S. aureus were identified. Most strains were resistant to penicillin (72%), and 3 isolates: 2 CN S. aureus and 1 coagulase-negative Staphylococci (CNS), were phenotypically resistant to vancomycin, oxacillin, and cefoxitin and were confirmed to carry mecA. Resistance to clindamycin, trimethoprim-sulfamethoxazole, and tetracycline was 23.9%, 30.4%, and 41.3%, respectively. Twelve isolates exhibited multidrug resistance; however, only one mecA positive strain among the three was typeable and belonged to spa type t2603. This study reports for the first time the presence of CN variant of MRSA, which was assigned the spa type t2603, and the presence of multidrug resistant S. aureus isolates from bovine milk in Morogoro, Tanzania.